# SOLUTION: A common mistake when solving equations is the following: The equation: 2(x -2) = x +3 First step in solving: 2x -2 =x +3 Write a clear explanation of what error has bee

Algebra ->  Algebra  -> College  -> Linear Algebra -> SOLUTION: A common mistake when solving equations is the following: The equation: 2(x -2) = x +3 First step in solving: 2x -2 =x +3 Write a clear explanation of what error has bee      Log On

 Algebra: Linear Algebra (NOT Linear Equations) Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Linear Algebra Question 65996: A common mistake when solving equations is the following: The equation: 2(x -2) = x +3 First step in solving: 2x -2 =x +3 Write a clear explanation of what error has been made. What could be done to avoid this error? Answer by uma(370)   (Show Source): You can put this solution on YOUR website!Given equation is 2(x-2) = x+3 The first step in solving this equation is to remove the parenthesis. This is done by multiplying each term inside the bracket by the term outside. ==> 2*x - 2*2 = x+3 The error committed here is that the multiplication of 2 by 2 has been forgotten. Only the first term is multiplied. To avoid this take care to multiply each term by the term outside as we say it aloud and work out. Good Luck!!!